Análise do cenário mundial do VE e os desafios da sua inserção na matriz energética brasileira - Feistel, Karin Rezende (2016)
This work aims to analyze the current situation of electric vehicles in the world, considering the factors that assisted their insertion in the world market and the public policies that are used to encourage this technology. Based on this analysis, is performed a prediction of a scenario in which electric vehicles are inserted in the Brazilian market through simulation results using the Monte Carlo Method a known and widespread mathematical method. Therefore, two cities are compared, a national pole of development and diversity, Sao Paulo, and the city known as the Capital of Electric Vehicle, Oslo, which will provide the information that will be used as a basis for the simulation. With this forecast, it is possible to predict an estimative of the environmental impact that replacing gasoline-powered vehicles for electric vehicles would bring to the environment. Furthermore, an analysis of energy impact in the Brazilian matrix is discussed and evaluated.